2004
DOI: 10.1080/00958970412331312652
|View full text |Cite
|
Sign up to set email alerts
|

Demetallation of a Ni(II) tetraazamacrocyclic complex by cyanoxime resulting in the formation of a stereospecific trinuclear compound [Na(H2O)6]+[NaNi2L6] (L = NC-C(NO)-C(O)NH )

Abstract: The reaction between the NiA(ClO 4 ) 2 and NaHL 2 {where A ¼ 14ane [N 4 ], the macrocyclic ligands derived from the product of template condensation of 2,6-diacetylpyridine with aliphatic 3,3 0 -diaminodipropylamine, NH 2 (CH 2 ) 3 NH(CH 2 ) 3 NH 2 ; and L ¼ 2-cyano-2-isonitrosoacetamide anion, ACO À (amidecyanoxime, NC-C(NO)-C(O)NH 2 À )} has led to the formation of a highly unusual trimetallic bis-[ fac-(triscyanoximato) nickel(II)] anionic complex anion instead of the expected Ni(II) macrocyclic complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The results of the EXAFS studies are shown in ESI 38,39 and demonstrate a very good fit (within 1 – 7 % values) between calculated and experimentally determined parameters of bond length and intera-tomic distances. The model used for the fit had a bidentate cyanoxime anion binding Pt, with the formation of a five-membered chelate ring in a fashion similar to that found in Pd(II) 36 and Ni(II) 65 cyanoximates. Determined by the EXAFS method and data fitting Pt-N and Pt-O bonds are slightly shorter than those experimentally observed in yellow monomeric Pt(PiPCO) 2 and Pt(MCO) 2 (Table 2), which may suggest a rather tighter binding of the equatorial cyanoxime anion to the metal center in the dark-green 1D polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the EXAFS studies are shown in ESI 38,39 and demonstrate a very good fit (within 1 – 7 % values) between calculated and experimentally determined parameters of bond length and intera-tomic distances. The model used for the fit had a bidentate cyanoxime anion binding Pt, with the formation of a five-membered chelate ring in a fashion similar to that found in Pd(II) 36 and Ni(II) 65 cyanoximates. Determined by the EXAFS method and data fitting Pt-N and Pt-O bonds are slightly shorter than those experimentally observed in yellow monomeric Pt(PiPCO) 2 and Pt(MCO) 2 (Table 2), which may suggest a rather tighter binding of the equatorial cyanoxime anion to the metal center in the dark-green 1D polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The water exclusion zones and the second coordination shells are marked by gray and blue rectangles, respectively. (B) Ultra-high-accuracy X-ray structures of Mg(H 2 O) 6 2+ (top) and Na(H 2 O) 6 + (bottom) illustrating similarities between Mg 2+ and Na + octahedral first hydration shells (Gerasimchuk and Dalley 2004;Hennings et al 2013). (C ) In scale schematic representation of the radius of the Mg(H 2 O) 6 2+ (green) and Na(H 2 O) 6 + (magenta) first cordination shells.…”
Section: Pdb Overview Of Direct Mg 2+ To Carbonyl Oxygen Atom (O B ) mentioning
confidence: 99%
“…36−38 There were only a few reported complexes of Cu and Ni with cyanoximes in general, with most of them being mononuclear compounds. 39−43 With the exception of one dicopper, 41 one stereospecific dinickel, 44 and one octa-iron 45 complex, no other homometallic or heterometallic complexes containing cyanoximes are reported. The 2-cyano-2-hydroxyimino-ethyl acetate, which is commercially known as "Oxyma" (HECO), and its analogous compound 2-cyano-2-hydroxyimino-methyl acetate (HMeCO) represent inexpensive and easily accessible compounds.…”
Section: ■ Introductionmentioning
confidence: 99%